Risk Factors of Drug Abuse among Adolescence - Liena Sofiana; Suci Musvita Ayu; Marsiana Wibowo; Erni Gustina; Satriawan Jaohandhy Muhtori (International Journal of Public Health Science (IJPHS), 2018)
Yogyakarta City, which is known as the center of education is a potential place for drug abuser to distribute illegal substance to the youth. It is evident in the great number of drug users in Yogyakarta City, in which 50% of them are adolescents and university students. The research aimed to know the relationships predisposing, enabling, and reinforcing factors and the drug abuse among adolescents in Yogyakarta City. The research employed cross sectional design. The samples were taken using multistage random cluster sampling. The data were taken through questionnaire given to 481 youth, at the age of 15-19 years in 18 senior high school and the equals in Yogyakarta City. The data were then analyzed using Chi Square test. Attitude, self-confidence, family role, and peer’s role are related to drug abuse. Knowledge, information sources, and teacher’s role are not related to drug abuse.